Harnessing Social Media for English Language Learning: Insights from an Islamic Senior High School Students in Eastern Indonesia - Anisah, Nur; Hasbullah, Hasbullah; Dabamona, Miftahulfadlik (Institut Agama Islam Negeri Palopo, 2025)
This study discusses how social media helps students learn English at a Madrasah Aliyah in Papua, Eastern Indonesia. The purpose of this study was to find out what social media are used by students and how they use them to learn. This study used a qualitative method with observation, interviews, and documentation. There were five students and one English teacher as respondents. The results showed that students often use Instagram, YouTube, and TikTok to learn. Instagram is used to do schoolwork, YouTube is used to learn grammar, while TikTok helps students increase their knowledge and improve their pronunciation. of the three applications, students prefer to use TikTok because they find it easier to understand lessons through interesting and not boring videos, compared to reading long texts or listening to direct explanations. Social media provides freedom in learning, makes students more enthusiastic, and more active in the learning process. Even so, the role of teachers remains very important to guide so that the use of social media continues to support learning goals. These results are in accordance with the theory that states that students will learn better if they feel free and motivated from within themselves. With good guidance, social media can help students improve their English skills.